Penyusunan Jenjang Karir Untuk Efektifitas Organisasi - Rifqi Dista Mardean; Erita Yuliasesti Diah Sari (Psyche 165 Journal, 2021)
This study aims to help organizations work more effectively than before by overcoming the existing problems in the Organization. The method used in this research is qualitative by using an open system approach and the assessment used to collect data is interviews, observation, and study of documents. This research was conducted at a coal mining company located in Jakarta. The data that has been collected will be integrated with the aim of completing the data found using other data collection methods. The problem that becomes the main point is the absence of role design and there is no career path scheme. This problem has an impact on the motivation to work down, difficulty in working, unable to work optimally and feel uncomfortable when working. Therefore it is necessary to design an appropriate intervention to overcome the impact of the above problems. The design of interventions carried out is the making of career paths